Optimisation of hybrid composite reinforced carbon and glass using AHP method - Mohd Daud, Mohd Ahadlin; Md Zahir, Nur Aizatul ‘Ain; Dhar Malingam, Sivakumar; Mansor, Muhd Ridzuan; Ab Ghani, Ahmad Fuad (Science and Technology Research Institute for Defence, 2019)
Aiming for the selection of carbon fibre reinforced polymer (CFRP) and glass fibre reinforced polymer (GFRP) hybrid composite with the best combination of strength, weight and cost, the analytical hierarchy process (AHP) method was applied. Ten composite configurations were arranged with different design criteria such as flexural strength, flexural modulus, strain to failure, density and cost and were then ranked by AHP method. AHP results revealed that C1with relative PV of 23.24% was the preferred hybrid composite for CFRP/GFRP design configuration. It was also concluded that the flexural strength of the design criteria was the most significant property which may affect the mechanical properties of the hybrid composite.